2021
DOI: 10.1177/09603271211054437
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane suppresses autophagy during the malignant progression of gastric carcinoma via activating miR-4521/PIK3R3 pathway

Abstract: Objective Sulforaphane, which exerts an effective anti-cancer ability, is a phytochemical converted from cruciferous plants. Here, we aimed to identify whether sulforaphane could suppress autophagy during the malignant progression of gastric carcinoma and to explore the underlying mechanisms. Methods SGC7901 cells were transfected with miR-4521 mimics, inhibitor, and pcDNA3.1- PIK3R3, and treated with sulforaphane or autophagy inhibitor. Cell proliferation, apoptosis, and miR-4521 or PIK3R3 expression were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Isorhamnetin induced GC cells autophagy via the PI3K pathway ( Li et al, 2021d ). Sulforaphane also suppressed cell autophagy during the progression of gastric cancer ( Mondal et al, 2016 ; Wang et al, 2021c ; Peng and Gu, 2021 ). Procyanidin exerted anti-cancer activity in GC by regulating autophagy ( Nie et al, 2016 ; Li et al, 2021c ).…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
“…Isorhamnetin induced GC cells autophagy via the PI3K pathway ( Li et al, 2021d ). Sulforaphane also suppressed cell autophagy during the progression of gastric cancer ( Mondal et al, 2016 ; Wang et al, 2021c ; Peng and Gu, 2021 ). Procyanidin exerted anti-cancer activity in GC by regulating autophagy ( Nie et al, 2016 ; Li et al, 2021c ).…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
“…It has been shown that SFN can inhibit GC cell autophagy through the activation of the miR-4521/PIK3R3 (phosphoinositide-3-kinase regulatory subunit 3) pathway. The mediator miR-4521-dependent apoptosis in vitro was also observed [111]. Sulforaphane has been shown to have proliferation inhibitory, cell cycle arrest, and apoptosis induction abilities in GC cells.…”
Section: Wasabimentioning
confidence: 76%
“…Subsequently, excessive free iron triggered ferroptosis in anaplastic thyroid cancer cells by inducing lipid peroxidation. Gastric carcinoma cells treated with sulforaphane exhibited increased levels of free iron, ROS, and MDA, as well as decreased levels of GSH and superoxide dismutase 2 (SOD2), indicating that this isothiocyanate triggers ferroptosis in cancer cells (Wen et al, 2023). Further studies have shown that sulforaphane activates PI3K and increases the expression of IRP2 and DMT1 in MGC‐803 cells, while PI3K inhibition eliminates the increase in IRP2 and DMT1 expression, indicating that sulforaphane inhibits the development of gastric carcinoma by regulating the PI3K/IRP2/DMT1 axis (Wen et al, 2023).…”
Section: Regulation Of Ferroptosis By Natural Productsmentioning
confidence: 99%
“…Gastric carcinoma cells treated with sulforaphane exhibited increased levels of free iron, ROS, and MDA, as well as decreased levels of GSH and superoxide dismutase 2 (SOD2), indicating that this isothiocyanate triggers ferroptosis in cancer cells (Wen et al, 2023). Further studies have shown that sulforaphane activates PI3K and increases the expression of IRP2 and DMT1 in MGC‐803 cells, while PI3K inhibition eliminates the increase in IRP2 and DMT1 expression, indicating that sulforaphane inhibits the development of gastric carcinoma by regulating the PI3K/IRP2/DMT1 axis (Wen et al, 2023). Furthermore, erianin extracted from Dendrobium chrysotoxum increased the N6‐methyladenosine modification of P53 and arachidonate 12‐lipoxygenase (ALOX12) mRNA by promoting methyltransferase‐like 3 (METTL3) expression, which enhanced ferroptosis in renal cancer stem cells by increasing the expression of these proteins (H. Shen et al, 2023).…”
Section: Regulation Of Ferroptosis By Natural Productsmentioning
confidence: 99%